A new subspecies of Delias agostina Hewitson (Lepidoptera: Pieridae: Pierinae) from Hainan Island - Lo, Yik-Fui Philip (Zootaxa, 2018)
The taxonomic status of the population of Delias agostina on Hainan Island is clarified and previous taxonomic treatments are reviewed. The insular population is found distinctive from continental races and is described herein as, Delias agostina sushii ssp. nov., a new subspecies endemic to Hainan Island. Notes on immature stages of the new taxon are also provided.